GRATITUDE PRACTICE AND PSYCHOLOGICAL WELL-BEING: A CORRELATIONAL STUDY - Nur Dian Seri Mohd Faizal; Errna Nadhirah Kamalulil; Teoh Hooi Ping (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study explores the correlation between gratitude practice and psychological well-being among Malaysian veterans. Veterans, having served in the military, often face psychological challenges such as post-traumatic stress and difficulty transitioning to civilian life, impacting their overall well-being. Despite the growing recognition of gratitude practice in improving psychological well-being, there remains a significant gap in research focused on Malaysian veterans. Existing studies primarily focus on Western veterans, neglecting the unique cultural and societal influences on well-being in Malaysia. The study aims to investigate the correlation between gratitude practice and the five components of the PERMA model: positive emotions, engagement, relationships, meaning, and accomplishment, as components of psychological well-being in Malaysian veterans. A quantitative cross-sectional design was employed, with 370 Malaysian veterans responding to a structured questionnaire. The Gratitude Questionnaire (GQ-6) and PERMA-Profiler were used to assess the correlation between gratitude practice and psychological well-being components. The findings revealed significant positive correlations between gratitude practice and all five components of the PERMA model, with the strongest correlation observed between gratitude practice and positive emotions (r = 0.766, p < 0.001), followed by meaning (r = 0.707, p < 0.001). This study confirms that gratitude practice significantly enhances psychological well-being among Malaysian veterans, promoting positive emotions, engagement and stronger social connections. Future research should incorporate mixed-method approaches to explore other influencing variables such as social support. Overall, gratitude practice is a valuable tool for improving the mental health and psychological well-being of veterans transitioning to civilian life.